Loopholed Scripts: A New Inquiry Approach for the Undergraduate Laboratory - Almeida Bauer Zytkuewisz, Matheus [UNESP]; Martins de Godoi, Denis Ricardo [UNESP]; Moura Bego, Amadeu [UNESP] (American Chemical Society (ACS), 2023)
This study’s general theme revolves around practical work in chemical education, and its scope is the employment of a novel inquiry strategy combined with a new openness level. We investigate how the controlled positive error, a new device for inquiry activities developed by us, affects undergraduate students’ experience of an experiment and develops their scientific mind after they attend a laboratory class. Qualitative research of the case study type was carried out. The subjects were first-year students enrolled in a general chemistry course. We employed textual documents and focus groups for data gathering and found that significantly changing the pattern of a laboratory activity, despite being a challenging and effortful task, had many benefits for the student’s development, such as increasing their connection to and proactivity toward the experiment.
Keywords: Chemical Education Research; Electrolytic/Galvanic Cells/Potentials; First-Year Undergraduate/General; Inquiry-Based/Discovery Learning